The Impact of the HDI, LFPR, RMW on Poverty in West Nusa Tenggara Province (NTB) During the Period 2016–2023 - Davi Wahyu Pratama; H.Sahri. MS; Ahmad Zaenal Wafik (Utan Kayu Publishing, 2025)
This study investigates the influence of the Human Development Index (HDI), Labor Force Participation Rate (LFPR), and District/City Minimum Wage (UMK) on poverty levels in West Nusa Tenggara Province (NTB) over the period 2016–2023. Employing a quantitative approach through panel data regression analysis, the findings reveal that both HDI and UMK exert a statistically significant impact on poverty, whereas LFPR does not demonstrate a significant effect. Specifically, HDI is found to have a positive and significant relationship with poverty, suggesting that enhancements in education quality, health services, and purchasing power contribute to poverty reduction. Conversely, UMK exhibits a significant negative correlation with poverty, indicating that increases in minimum wages, when not accompanied by the generation of productive employment opportunities, may inadvertently exacerbate poverty levels. The insignificance of LFPR implies that labor force participation alone does not directly influence poverty alleviation in the region. These findings offer valuable insights for the formulation of more targeted and integrative policy interventions aimed at eradicating poverty in NTB.